Practical strategies to improve national competitiveness - Denis Syromyatnikov; Pavel Konev; Mikhail Popov; Naila Sultanova (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Today, the global community is faced with a new vision of the economy that aims to coordinate public policies with the purpose of ensuring sustainable growth to facilitate economic recovery under the current conditions and after the COVID-19 pandemic. The purpose of the study is to create a basic typology of strategies to improve national competitiveness in the context of globalization. The research methodology includes a comparison of economic development models and strategies for different countries around the world and an analysis of data from international organizations. The benchmarking of national strategies is based on the measurements' evaluation for three groups of the GCI index components. The originality of the study stems from the fact that it proposed choosing a strategy for the development of the national economy with account taken of the level of its economic development. The strengths and weaknesses of competitiveness in the profile of the economy are identified and, whereby, a strategy to increase national competitiveness is chosen, according to the results of this analysis. The results of the study showed that the American model of economic development is the most competitive one among the examined models. In addition, the paper shows that the application of practical strategies for social integration, as well as mergers and acquisitions, will contribute to enhancing the national competitiveness in the context of economic growth and raising the living standards of the population. The findings of this research provide practical guidance for related professionals attempting to choose a suitable public policy to form effective and holistic national strategies and monitor the country's progress over time.
Keywords: F01; F63; M21; 330; Market globalization; Identity politics; Optimal balance; Strategic decisions; Economic models